Bimbingan Karir Kolaboratif dalam Pemantapan Perencanaan Karir Siswa SMA - Afdal Afdal; M Suya; Syamsu Syamsu; Uman Uman (Jurnal Konseling dan Pendidikan, 2014)
Individual career development along the life span is integrated in each role, setting, events in life and is influenced by many factors. One of the factors that affect the development of the individual's career is a family environment. At issue now is the development of a career is not a major concern for parents. Parents consider issues relating to the development of careers is the responsibility of the teacher at the school, particularly teachers of guidance and counseling. The problem becomes when the teacher/counselor who understands the BK and understand deeply about children and career progression does not perform activities of collaboration/cooperation with parents to jointly realize the optimal child development careers so it is able to take decisions appropriately and independently with regard to education and career in the future. This paper discusses the basic concept of collaborative career guidance, career guidance principles and collaborative implementation of collaborative career guidance to establish career planning high school students.